MODEL OF OPERATION OF COMBAT AIRCRAFT GROUND TRANSPORTATION SERVICE SYSTEMS: Array - Nagornyy, Y.; Kalinichenko, O.; Pavlenko, O. (Municipal economy of cities. Series: «Economy science», 2021)
The article analyzes the current state and prospects of development of systems of ground transport maintenance of aircraft, which allowed to form the purpose of the study in this development. The chosen topic is quite relevant, because effective organization of combat aircraft maintenance allows raising combat effectiveness of Ukrainian air forces. One of the directions of maintenance cost reduction is effective use of resources. The study establishes that in order to improve the quality of transport maintenance and increase the combat effectiveness of the Armed Forces and National Guard of Ukraine, it is necessary to pay attention to the use of new transport vehicles, especially modular designs and development of technology to determine the optimal distribution of transport resources for aircraft maintenance, for different conditions of the transport complex and different types of aircraft maintenance. The authors propose to consider two aircraft maintenance schemes – existing using existing technology and proposed using a modular design. In a modular design, a wheeled tractor acts as a tug, which drives mobile modules, which are special means for servicing aircraft. Such an energy-efficient vehicle may consist of 4 modules at a time. The process of delivering the cargo required for servicing the aircraft at the airport is estimated at costs, which form a set of cost values for each technological process of servicing the aircraft. The set criterion is influenced by the parameters: the cost of performing a unit of the corresponding operation, the cost of one hour of work of one worker, the time of performing the corresponding operation, the number of modules involved to perform the corresponding service, the number of aircraft. The developed models of functioning of combat aircraft maintenance systems for maintenance will allow to take into account the influence of random factors, to assess the possibility of using modular designs, as well as to determine the efficiency of existing resources on airfields in Ukraine.